GenAI in Occupational Therapy: A Survey of Adoption, Ethical Concerns, and Training Needs - Adam Lockwood; Ryan Farmer; Tara Mansour (American Journal of Occupational Therapy, 2026)
Importance Occupational therapy practitioners are rapidly adopting generative artificial intelligence (GenAI) tools in clinical settings, yet little is known about current usage patterns, ethical concerns, or training needs specific to the profession. Objective To examine how occupational therapy practitioners are using GenAI in practice and explore their ethical concerns, and training needs. Design Cross-sectional survey study. Participants 277 occupational therapists; 77 occupational therapy assistants with a mean age of 40.8 years and a mean of 14.8 years of occupational therapy practical experience. Outcomes and Measures Self-report questionnaire examining AI usage patterns, perceived advantages and limitations, ethical and institutional factors influencing adoption, and training preferences. Results 48.9% of participants reported using GenAI in the past 6 months, with common applications including answering work-related questions (38.7%) and generating clinical content. Primary concerns included preference for human judgment (46.2%), accuracy and reliability (45.7%), and ethical issues (38.2%). Only 6.2% reported formal institutional GenAI policies, and 94.8% never entered personally identifiable information into GenAI systems; only 12.2% obtained informed consent from clients, caregivers, or other relevant parties to use GenAI. While 68.3% believed practitioners should receive GenAI training, 42.2% reported receiving no training, with most (73.2%) desiring formal webinar-based instruction. Conclusions and Relevance Occupational therapy practitioners reported significant GenAI use. Participants also noted substantial concerns about ethical implementation, data security, and loss of clinical skills. Findings suggest that critical gaps in formal training and institutional guidance exist. Evidence-based frameworks and structured educational initiatives to ensure GenAI integration aligns with client-centered, ethical practice standards are needed.